Reducing Effect of Hypnotherapy Anxiety in Pregnant Women - Marni Siregar; Hetty WA Panggabean (Jurnal Penelitian Pendidikan IPA, 2024)
Pregnant women experience feelings of uncertainty, namely positive and negative feelings about the presence of the baby. Positive feelings are in the form of happiness that is expressed freely and do not cause feelings of guilt, and negative feelings are feelings of anxiety about the pain that will occur during childbirth. The third trimester is the peak of the emotional excitement of the birth of a baby. The third trimester is often called the waiting and alert period because at that time the mother can't wait for the birth of her baby. Sometimes mothers worry that their baby will end at any time. The aim of this research is to determine the effect of hypnotherapy on the anxiety of pregnant women at the Siatas Barita Community Health Center, North Tapanuli Regency in 2022. Research Method, This research is a Quantitative research with the research design used is Quasi Experiment with a one group pre test and post test design. A total of 40 pregnant women were taken from Siatas Barita Health Center, North Tapanuli Regency in 2022. Hajil Research. The Wilcoxon test from one group pre test and post test obtained a ρ - value of 0.01, which means that there is an effect of hypnotherapy on reducing the anxiety of pregnant women before and after treatment. The ρ value in this study is 0.01, which is smaller than 0.05, so there is an influence of hypnotherapy to reduce the anxiety of pregnant women at the Siatas Barita Health Center, North Tapanuli Regency in 2021. This shows that Ha was accepted, which means there was an influence of hypnotherapy after the intervention was carried out. Conclusion. There is an effect of hypnotherapy on reducing anxiety in pregnant women, where the Wilcoxon test results have a value of ρ = 0.00 (ρ < 0.05).